Case Report: A Novel Compound Heterozygote Mutation of the SCNN1B Gene Identified in a Chinese Familial Pseudohypoaldosteronism Disease Type I With Persistent Hyperkalemia - Liu, Zongzhi; Wang, Xiaojiao; Zhang, Zilong; Yang, Zixin; Wang, Junyun; Wang, Yajuan (Frontiers in Pediatrics, 2022)
Background: Pseudohypoaldosteronism (PHA) diseases are difficult to diagnose because symptoms are often non-specific and an in-depth pathogenesis study is still lacking. Case Presentation: we present the case of a 19-day-old neonate who presented with unexplained recurrent hyperkalaemia, hypovolemia and metabolic acidosis, whose parents did not have significant clinical disease characteristics. Whole-exome sequencing was performed to confirm the disease and genetic pattern of the neonate. Sanger sequencing was performed to identify the mutation sites. Secondary structure comparisons and 3D model construction were used to predict changes in protein structure. Two novel frameshift mutations in the SCNN1B gene were identified (c.1290delA and c.1348_1361del), which resulted in amino acid synthesis termination (p.Gln431ArgfsTer2 and p.Thr451AspfsTer6). Considering the clinical phenotype and genetic analysis, this case was finally identified as a PHA type I disease. Genetic analysis showed that the neonate suffered complex heterozygosity in the SCNN1B gene inherited from the parents, which is passed on in an autosomal recessive inheritance pattern. These two deleterious mutations resulted in an incomplete protein 3D structure. Conclusions : Our results have confirmed the associations of mutations in the SCNN1B gene with recurrent hyperkalaemia, which can cause severe PHA type I disease, meanwhile suggested clinical attention should be paid when persistent recurrent hyperkalemia is accompanied by these type of mutations.